The Effects Of Online Listening Activities On Auditory Comprehension Of Efl A1 Learners In An Ecuadorian University - Espol (2017)
Auditory skills are a fundamental social component in the process of english language learning (ell), yet the students’ greatest difficulty is to understand conversations in english. Therefore, this study aims to determine the effectiveness of online listening activities on students’ auditory skills. Thus, we decided to make an intervention at a private university located in a coastal province of ecuador. This intervention was conducted with undergraduate students to whom learning english is mandatory. The university offers the students various services such as the access to both internet service and virtual platforms. These virtual platforms allow the students to have access to a variety of online activities to learn english more quickly and effectively. The action research paradigm was implemented to verify this problem. Consequently, in order to solve the problem, we decided to use the moodle virtual platform.